Explaining differences in efficiency among dairy operations - Berends, P. T.; Langemeier, Michael R.; Featherstone, Allen M. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
To remain competitive, dairy operatoins need to continue to improve production efficiency and manage costs. Kansas Farm Management Association data from 1991 to 1995 were used to measure technical, economic, and overall efficiencies for 50 dairy operations in Kansas. On average, the farms showed .87 technical, .71 economic, and .67 overall efficiency. The latter was related negatively to labor, capital, feed, and fuel and utility expenses per cow. Veterinarian expenses were related positively to overall efficiency. Overall efficiency was the most sensitive to changes in feed expenses per cow, emphasizing the importance of controlling this cost. Results also indicated that a larger proportion of overall inefficiency was due to cost control problems than to an inefficient herd size
Keywords: Dairy; Efficiency; Profitability